COVID-19-induced psychosis: two case reports and narrative literature review - Karakuła, Kaja Hanna; Nowacka, Olga; Ryczkowski, Aleksander; Sitarz, Ryszard; Forma, Alicja; Juchnowicz, Dariusz (Current Problems of Psychiatry, 2022)
Introduction. SARS-CoV-2 infection might be presented in many various specific and non-specific manifest and symptoms from different systems. Also, the psychotic symptoms are documented but the explanation for their pathophysiology remains debatable and a complex matter. The main objective of this paper is to present cases of patients without a history of psychiatric disorders who developed the first episode of psychosis during the SARS-CoV-2 infection. Material and methods. Two cases of not-related patients with no previous psychiatric history developed psychotic episodes during COVID-19 infection. In both cases chronologically first they experienced symptoms of infection, secondly, delusions and psychomotor agitation that required psychiatric hospitalization. Full remission was observed after antipsychotic treatment in both cases. Results. Even though the pathophysiology of the post-COVID-19 psychiatric symptoms remains unclear, some reports that indicate associations between the infection and the onset of such symptoms. The infection itself, by the induction of cytokine storm followed by the excessive release of pro-inflammatory cytokines, is considered to stimulate the potential onset of the psychosis, however, other factors such as medications used during treatment (with a particular emphasis on glucocorticosteroids) or psychological factors should be considered as well. Conclusions. Patients infected with SARS-CoV-2 might develop serious psychotic episodes even without a prior psychiatric history. Besides, psychiatric symptoms might be the first the even the only manifestations associated with the active SARS CoV-2 infection which seems to be very challenging especially in cases of rapid psychotic episodes without any clear respiratory symptoms.